2020
DOI: 10.48550/arxiv.2009.11487
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isotropic-Nematic Phase Transition and Liquid Crystal Droplets

Abstract: Liquid crystal droplets are of great interest from physics and applications. Rigorous mathematical analysis is challenging as the problem involves harmonic maps (and in general the Oseen-Frank model), free interfaces and topological defects which could be either inside the droplet or on its surface along with some intriguing boundary anchoring conditions for the orientation configurations. In this paper, through a study of the phase transition between the isotropic and nematic states of liquid crystal based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It is worthy to mention that recently Golovaty et al [15,14] studied a model problem based on highly disparate elastic constants. Most Recently, Lin-Wang [22] studied isotropic-nematic transitions based on an anisotropic Ericksen's model. (2.16)…”
Section: Resultsmentioning
confidence: 99%
“…It is worthy to mention that recently Golovaty et al [15,14] studied a model problem based on highly disparate elastic constants. Most Recently, Lin-Wang [22] studied isotropic-nematic transitions based on an anisotropic Ericksen's model. (2.16)…”
Section: Resultsmentioning
confidence: 99%
“…The proof here is inspired by the density argument in [23]. It is worth mentioning that the use of density argument to prove weakly lower-semincontinuity like (5.20) was first employed in [12].…”
Section: Estimates Of Level Setsmentioning
confidence: 99%
“…On the other hand, Theorem 1.1 can be considered as a dynamical version of a recent work by Golovaty et al [13]. Concerning the method we use, at least in obtaining the anchoring boundary condition (1.17c) which is one of the main novelty in this work, we are inspired by a recent work of Lin-Wang [23]. There the authors studied isotropic-nematic transitions based on an anisotropic Ericksen's model.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth to point out that the Problems A, B and C thus presented were all derived from a phenomenological theory, see [24] and [6]. In a recent work [21], it is shown that one can rigorously establish these model problems from a general theories of Ericksen (for liquid crystals with variable degree of orientations [7]) or from the de Gennes-Landau model of liquid crystals [8] in suitable physical regimes.…”
mentioning
confidence: 94%